2020
DOI: 10.2147/ott.s234819
|View full text |Cite
|
Sign up to set email alerts
|

<p>TUG1 Promoted Tumor Progression by Sponging miR-335-5p and Regulating CXCR4-Mediated Infiltration of Pro-Tumor Immunocytes in CTNNB1-Mutated Hepatoblastoma</p>

Abstract: Introduction: HB presents with the highest frequency of CTNNB1 mutations, resulting in activation of Wnt signaling pathway. A number of studies have demonstrated CTNNB1 mutation contributed to the development of HB. However, limited research explored the function of lncRNAs in HB with CTNNB1 mutation. Methods: We screened lncRNA expression profiles in CTNNB1-mutated HB samples and identified lncRNAs associated with malignant phenotype in HB. The association between lncRNA and immune microenvironment was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…miR‐622 is regulated by the enhancer of zeste homolog 2 (EZH2), which causes the down‐regulation of miR‐622 through the H3K27 trimethylation methylation‐related silencing of the promoter in hepatocellular carcinoma. In accordance with these data, Xie et al reported that up‐regulation of miR‐335 led to reduced expression of CXCR‐4 in HepG2 cells (Xie et al., 2020).…”
Section: Discussionmentioning
confidence: 56%
“…miR‐622 is regulated by the enhancer of zeste homolog 2 (EZH2), which causes the down‐regulation of miR‐622 through the H3K27 trimethylation methylation‐related silencing of the promoter in hepatocellular carcinoma. In accordance with these data, Xie et al reported that up‐regulation of miR‐335 led to reduced expression of CXCR‐4 in HepG2 cells (Xie et al., 2020).…”
Section: Discussionmentioning
confidence: 56%
“…In breast cancer cells, neutralizing NRP2 antibody blocked cytoplasmic C-X-C Motif Chemokine Receptor 4 ( CXCR4 ) expression which was followed by decreased tumor cell migration ( 22 ). Interestingly, upregulation of CXCR4 was recently associated with the infiltration of pro-tumorigenic macrophages, neutrophils, and dendritic cells in HB tissue samples ( 58 ). Considering the NRP2-CXCR4 axis, NRP2 targeting might attenuate the growth of HB at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“… 71 By sponging miR-335 and regulating CXC chemokine receptor 4 (CXCR4), lncRNA TUG1 promotes tumor progression in CTNNB1-mutated hepatoblastoma. 111 LncRNA RP11-436H11.5, functioning as an endogenous sponge for miR-335, upregulates BCL-W by sponging miR-335 and promotes proliferation and invasion in RCC. 60 In bladder cancer, lncRNA SLCO4A1-AS1 promotes proliferation and migration by regulating the miR-335/OCT4 axis.…”
Section: Factors Modulating Mir-335 In Cancersmentioning
confidence: 99%